Methionine kinetics in adult men: effects of dietary betaine on L-[2H3-methyl-1-13C]methionine - Storch, K.J; Wagner, D.A; Young, V.R (The American journal of clinical nutrition, 1991)
The effects of a daily 3-g supplement of betaine on kinetic aspects of L-[2H3-methyl-1-13C]methionine (MET) metabolism in healthy young adult men were explored. Four groups of four subjects each were given a control diet, based on an L-amino acid mixture supplying 29.5 and 21.9 mg.kg-1.d-1 of L-methionine and L-cystine for 4 d before the tracer study, conducted on day 5 during the fed state. Two groups received the control diet and two groups received the betaine supplement. Tracer was given intravenously (iv) or orally. The transmethylation rate of MET (TM), homocysteine remethylation (RM), and oxidation of methionine were estimated from plasma methionine labeling and 13C enrichment of expired air. RM tended to increase (P = 0.14) but the TM and methionine oxidation were significantly (P 0.05) higher after betaine supplementation when estimated with the oral tracer. No differences were detected with the intravenous tracer. Methionine concentration in plasma obtained from blood taken from subjects in the fed state was higher (P 0.01) with betaine supplementation. These results suggest that excess methyl-group intake may increase the dietary requirement for methionine